CSC752: Advanced Algorithm & Analysis / College of Computing, Informatics and Media - UiTM, College of Computing, Informatics and Media (Universiti Teknologi MARA (UiTM), 2022)
Algorithmic problems form the core of computer science, and thus algorithm design and analysis is among its most fundamental elements. This course focuses on the clean mathematical modeling of real-world problems, identifying the appropriate advanced algorithm design techniques to these problems, and analyzing these algorithms. This is done by exploring a variety of real-world problems in various applications, including optimization and combinatorial problems. The algorithm design techniques topics and applications include divide and conquer, greedy algorithms, dynamic programming, network flow, NP-complete, approximation and other advanced algorithms.